Pool boiling heat transfer enhancement using the micro-thick metallic foam surface in saturated water - Lim, Hyunmuk; Doh, Su Yoon; Choi, Junyoung; Moc, Jungchan; You, Seung M.; Lee, Jungho (International Communications in Heat and Mass Transfer, 2024)
Pool boiling experiments using micro-thick metallic foam (MMF) are performed in saturated water at atmospheric pressure. Sintered experimental samples were fabricated with micro-thick metallic foam instead of soldering for the rigorous pool boiling experiments. This study provides the heat transfer coefficient and the critical heat flux (CHF) of the metallic foam surfaces for different pore densities and thicknesses. Also, the boiling mechanism and bubble dynamics on the micro-thick metallic foams for pool boiling were investigated with their visualization. As a result, the MMF surface with 200 μm thick and 130 PPI has a CHF of 2050 kW/m2 and a heat transfer coefficient of 273.6 kW/m2∙K, respectively. Compared with other surface modification methods, MMFs with a thickness of about 200 μm to 300 μm can enhance heat transfer characteristics and increase the CHF. In particular, the increase in CHF might be attributed to the highly permeable structure of the metallic foam. Therefore, this study presents valuable insight into a feasible material-insensitive heat transfer enhancement method for pool boiling.
Keywords: Boiling heat transfer enhancement; Bubble behavior; Heat transfer co-efficients; Heat Transfer enhancement; Metallic foam; Micro-thick metallic foam; Pool boiling; Pool boiling heat transfer; Pore densities; Saturated water; Bubble behavior; Critical heat flux; Heat transfer enhancement; Micro-thick metallic foam; Pool boiling